Construction of the problem of Latin gangs in Spain and response of the law enforcement system - Kazyrytski, Leanid (European journal on criminal policy and research, 2017)
Recently, since their official recognition as criminal organizations by Spanish law enforcement authorities, stricter prosecution of Latin street gangs has been observed. The toughening of legal regulations, new models of police conduct and the increasingly active role of prosecutors have contributed to greater punitive pressure on the gangs. This article has two main objectives: first, to describe changes in Spanish criminal policies for the treatment of Latin American street gangs; second, to analyse to what extent these changes are in consonance with empirical findings on criminal involvement and the organizational nature of these groups. The results show that despite the recent increase in criminal activity these groups cannot be viewed as the only parties to blame for local street crime. The opinion of the law enforcement authorities that Latin American street gangs are a form of organized crime is far from reality. These groups do not have the required combination of characteristics inherent to criminal organizations, and their purposes are not always exclusively criminal.